Rural Melodrama, the Western, and the Politics of National Reconciliation in Juan Antonio Bardem's La venganza (1958). - Mourenza, Daniel (Hispanic Research Journal, 2022)
When La venganza was premiered at Cannes, critics reviewed the film negatively in comparison with Juan Antonio Bardem's previous films and vis-à-vis the aesthetics of Italian neorealism. This article claims that such a criticism was misguided from the outset and that this film should be analysed as a rural melodrama, a genre particularly prolific in the 1950s. Furthermore, like many other Spanish rural melodramas, La venganza incorporates visual and dramatic motifs from the western to tell a story of revenge and, ultimately, reconciliation. Scholars have taken for granted that this film is an allegory of the Politics of National Reconciliation approved by the Communist Party of Spain in 1956, but have seldom discussed these politics regarding its use of genre. This article addresses how and why Bardem used the genres of the rural melodrama and the western to convey such a political message.